2016
DOI: 10.1371/journal.pone.0166178
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium Reduces Liver Injury in Mice on a High-Fat Diet: Alterations in Microbial and Bile Acid Profiles

Abstract: A high-fat “Western-style” diet (HFWD) promotes obesity-related conditions including non-alcoholic steatohepatitis (NASH), the histologic manifestation of non-alcoholic fatty liver disease (NAFLD). In addition to high saturated fat and processed carbohydrates, the typical HFWD is deficient in calcium. Calcium-deficiency is an independent risk factor for many conditions associated with the Western-style diet. However, calcium has not been widely evaluated in the context of NAFLD. The goal of the present study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 68 publications
2
25
0
Order By: Relevance
“…while reducing Bifidobacterium spp. in healthy men or mice (Nadeem Aslam et al, 2016; Trautvetter et al, 2018; Li et al, 2019). The impact of dietary supplementation with selenium, magnesium, iron or zinc on certain gut commensal or pathogenic microbes was also reported in children and mice (Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…while reducing Bifidobacterium spp. in healthy men or mice (Nadeem Aslam et al, 2016; Trautvetter et al, 2018; Li et al, 2019). The impact of dietary supplementation with selenium, magnesium, iron or zinc on certain gut commensal or pathogenic microbes was also reported in children and mice (Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the medications of initial therapy in PNS included the compound of vitamin D3 and calcium carbonate. Lactococcus significantly enriched in adults treated with vitamin D3 for 12 weeks, and calcium supplementation could also increase the numbers of intestinal microbiota such as Ruminococcaceae,Akkermansia and Turicibacter [29, 30]. Therefore, the combination of prednisone, compound of Vitamin D3 and calcium carbonate might have a synergistic effect on gut microbiota in patients with PNS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, calcium seems to have a role in NASH pathogenesis and development: a 2016 research by Aslam et al showed that, in HFD diet-feed mice with calcium supplementation for 18 months, compared to only HFD diet mice, the first one had low inflammation and fibrosis, together with a reduced NAS score at histology. That was explained by its action on gut microbiota, that in calcium supplemented mice appeared to be colonized especially by Ruminococcaceae and Akkermansia, known to be associated with the so-called “healthy gut” for degrading polyglucans and for their action on lipid metabolism, but also by reducing total biliary acids pool (especially taurine-conjugated β-muricholic acid (MCA) and main murine biliary acid) that demonstrated to have citotossic capacity in NASH when present in high concentrations [ 72 ].…”
Section: Discussionmentioning
confidence: 99%